Lyle the kindly viking - Big Idea Productions; Warner Home Video (Firm) ([Chicago] : Big Idea Productions ; Burbank, Calif. : Distributed in the USA and Canada by Warner Home Video, 2003)
Assisted by those rascally French Peas, Archibald aims for new heights in "veggie programming" by attempting to produce "the world's first all-vegetable staging of Shakespeare's Hamlet," the first-ever "Classy songs with Larry," and for the grand finale, the world premier of what he believes to be Gilbert and Sullivan's "lost musical"--"Lyle, the kindly Viking!"
"A lesson in sharing"--Container.
Bonus features: over two hours of family fun: Lyle trivia; family activity "Boiling river"; behind the scenes; progression reel; Veggie karaoke; DVD-ROM fun; game "Storyboard shake-up"; phone message; interactive storybook; "Easter egg" hidden features; eight chapter selects of favorite scenes; Dolby digital 5.1 surround sound. Includes the silly song: Larry's high silk hat.
Director, Tim Hodge ; writter, Phil Vischer ; producer, Jennifer Combs.
Voices Lisa Vischer, G. Bock, Phil Vischer, Mike Nawrocki, Pea Monks.
Ages 3 and up.
DVD, stereo, Dolby digital 5.1 Surround sound.
Keywords: Sharing -- Juvenile films; Video recordings for the hearing impaired